KONSEP AL-QUR’AN DAN HADIST TENTANG RIBA DAN BUNGA BANK - Meriyati, Meriyati; Nugraha, Sarah Lutfiyah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
Riba is an activity of exploitation and does not use the concept of ethics or morality. Allah SWT forbids transactions that contain elements of usury, this is due to oppressing others and the presence of elements of injustice (unjustice). Since pre-Islamic usury has been known and even often carried out in daily economic activities. At the time of the Prophet Muhammad SAW usury began to be prohibited with the revelation of the verses of the Qur'an which stated the prohibition of usury, these verses were revealed according to the time and period of the revelation of the verse until there was a verse that strictly forbade it. The practice of usury is not only prohibited by Islam, but religions outside of Islam also prohibit it. The scholars agreed and stated firmly about the prohibition of usury, in this case referring to the Book of Allah and the Sunnah of the Prophet as well as the consensus of the scholars. Broadly speaking, there are two types of usury, namely usury due to accounts payable and usury due to buying and selling. The modernists view usury as emphasizing the morality aspect, not the formal legal aspect, but they (the modernists) do not allow usury-taking activities. Islam has forbidden usury in QS Ar Rum: 39, An Nisa ': 160 - 161, Ali Imran: 130 - 131, and Al Baqarah: 275 - 280.Keyword: Riba, the Law of Riba, the Qur'an and HadithÂ